2 Ablation of scar-related ventricular tachycardia: paced electrogram feature analysis (PEFA) is a novel and effective substrate based strategy. (16th October 2019) - Crinion, D; Hassan Shariat, M; Baranchuk, A; Simpson, C; Gupta, D; Hashemi, J; Gul, EE; Abdollah, H; Enriquez, A; Glover, B; Redfearn, D
Abstract : Background: Ablation of scar related ventricular tachycardia (VT) has been shown to be superior to escalation of drug therapy. However, the incremental benefit remains modest, with 42% experiencing recurrent shocks and 64% appropriate anti-tachycardia pacing (ATP) in the VANISH study. Furthermore, VT induction to allow activation mapping and entrainment is not tolerated in 70% of cases. Improved substrate based ablation strategies are needed. Paced electrogram feature analysis (PEFA) is a novel and promising technique. This method utilizes close coupled extra-stimuli to reveal latency and increased electrogram (EGM) duration (figure 1 ) that is evident at critical VT isthmus(es) (figure 2 ). Purpose: To investigate the effectiveness of PEFA based VT ablation. Methods: A single centre, prospective study. Consecutive cases of scar related VT that had an implantable cardiac defibrillator (ICD) and no prior ablations were recruited. Close coupled pacing was performed at the right ventricular apex (VERP + 50 ms) and the VT isthmus(es) identified on high density mapping catheters (HD Grid™ or Reflexion™, St Jude) by increased electrogram (EGM) duration and latency (figure 1 ). An algorithm was developed to identify the latest EGM component after the S2 pacing artefact (St Jude EnSite Precision Electroanatomic Mapping). The amplitude sensitivity was set at 0.05 mV and manual assessment was used to correct the automated annotation when visibly inaccurate. This millisecond value was displayed on the geometry as a colour (PEFA map) (figure 2 ). PEFA identified VT isthmus sites were targeted for ablation (figure 1 ). The PEFA map was repeated to ensure comprehensive abolition. VT stim protocol with three extra-stimuli was performed at the end of each case. Follow up ICD interrogation data was utilized to assess for VT recurrence and mortality. Results: A total of 23 cases were recruited. table 1 provides an overview of baseline characteristics. table 2 includes procedure details and outcomes. Conclusion: PEFA based VT ablation is feasible and effective. A high proportion of cases were non-inducible, with low VT recurrence rates. This is the largest dataset to date on PEFA based VT ablation, the first to include non-ischaemic aetiologies, and reports a longer mean follow up. PEFA appears to be a promising substrate based VT ablation strategy.